A candidate DNA vaccine elicits HCV specific humoral and cellular immune responses - Zhu, Li-Xin (World J Gastroenterol, 2004)
AIM: To investigate the immunogenicity of candidate DNA vaccine against hepatitis C virus (HCV) delivered by two plasmids expressing HCV envelope protein 1 (E1) and envelope protein 2 (E2) antigens respectively and to study the effect of CpG adjuvant on this candidate vaccine. METHODS: Recombinant plasmids expressing HCV E1 and E2 antigens respectively were used to simultaneously inoculate mice with or without CpG adjuvant. Antisera were then collected and titers of anti-HCV antibodies were analyzed by ELISA. One month after the last injection, animals were sacrificed to prepare single-cell suspension of splenocytes. These cells were subjected to HCV antigen specific proliferation assays and cytokine secretion assays to evaluate the cellular immune responses of the vaccinated animals. RESULTS: Antibody responses to HCV E1 and E2 antigens were detected in vaccinated animals. Animals receiving CpG adjuvant had slightly lower titers of anti-HCV antibodies in the sera, while the splenocytes from these animals showed higher HCV-antigen specific proliferation. Analysis of cytokine secretion from the splenocytes was consistent with the above results. While no antigen-specific IL-4 secretion was detected for all vaccinated animals, HCV antigen-specific INF-γ secretion was detected for the splenocytes of vaccinated animals. CpG adjuvant enhanced the secretion of INF-γ but did not change the profile of IL-4 secretion. CONCLUSION: Vaccination of mice with plasmids encoding HCV E1 and E2 antigens induces humoral and cellular immune responses. CpG adjuvant significantly enhances the cellular immune response.